(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the theoretical and methodological foundations for improving organizational and managerial mechanisms for the formation of social creativity in future education managers and the tasks of forming social creativity in future education managers based on advanced foreign experience. Modern models of organizational and managerial mechanisms in higher educational institutions are also analyzed.